The Role Of Internet Financial Reporting Elements In Mediating Systematic Risk And Debt Policy As An Effort To Increase Firm Value - Benediktus Ardie Reho; Sari Rahmadhani (UNIVED Press, 2024)
This study aims to analyze the ability of Internet Financial Reporting (IFR) to mediate the relationship between debt policy and systematic risk to fixed values. The research data is companies that are in the order of LQ45 listed on the Indonesia Stock Exchange in 2018-2022. Analysis of the path with the lowest square partially shows the IFR element as a mediator. The test results show that debt policy is detrimental to fixed value and systematic risk has no effect on fixed value. Both debt and risk policies have a positive effect on IFR. The practical implication of the results of this study is that the role of IFR as a mediator occurs when the company has the completeness of IFR elements, namely content, technology, time feasibility, and convenience for users. The role of IFR is very important to be able to increase the value of the company by giving positive signals to investors who make decisions. Companies must pay attention to elements of technology and user support so that IFR can function optimally to increase firm value.